2003
DOI: 10.1002/clc.4960260303
|View full text |Cite
|
Sign up to set email alerts
|

Understanding implantable cardioverter defibrillator shocks and storms: Medical and psychosocial considerations for research and clinical care

Abstract: Summary:The experience of shock is the distinguishing feature for patients with implantable cardioverter defibrillators (ICDs) and is associated with diminished psychological functioning and quality of life. Multiple shocks and ICD storm are a relatively common event among patients with ICDs (10-20%) and may present specific challenging medical and psychological management for the attending health care providers. This paper examines the medical and psychological aspects of ICD shocks and storms and describes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
0
11

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 28 publications
1
111
0
11
Order By: Relevance
“…For a more complex discussion of the presentation and management of general anxiety and depression in ICD patients, please refer to Sears and Conti. 26 The Value of a PTSD Diagnosis: Theoretical…”
Section: Prevalence and Clinical Impact Of Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…For a more complex discussion of the presentation and management of general anxiety and depression in ICD patients, please refer to Sears and Conti. 26 The Value of a PTSD Diagnosis: Theoretical…”
Section: Prevalence and Clinical Impact Of Ptsdmentioning
confidence: 99%
“…26,32 These risk markers provide the clinician with an initial method of identifying patients who may warrant further assessment of psychosocial distress.…”
Section: Clinical Management Of Psychosocial Distress Identification mentioning
confidence: 99%
“…17 Recent research has also identified other factors salient to quality of life in ICD recipients in addition to anxiety and depression, as evidenced by the fact that approximately 32% of recent articles have examined these constructs. Recipients of ICDs who are female or young (< 50 years of age) are more likely to develop anxiety, depression, or other distress symptoms.…”
Section: Patient Factors In Implantable Cardioverter Defibrillator Rementioning
confidence: 99%
“…16,18 Patients who experience a greater number of shock discharges, whether cumulatively across time or within short periods of "ICD Storm," (≥ three shocks in 24 h) are also more likely to experience such symptoms that lower quality of life. 17,19,20,21 As ICD recipients have a more optimistic disposition and higher positive expectations for undergoing ICD therapy, their quality of life is either maintained or improves. 22 Also, patients with ICDs who adopt catastrophic cognitions regarding their cardiac functioning experience higher rates of anxiety specific to a fear of being shocked.…”
Section: Patient Factors In Implantable Cardioverter Defibrillator Rementioning
confidence: 99%
“…Adults with ICDs have significantly higher levels of depression and anxiety, [1][2][3][4][5] and frequent ICD discharges in adults have been associated with even higher risk for depression and anxiety. 6 However, studies on children and adolescents with ICDs are limited. [7][8][9][10][11] DeMaso and colleagues 12 found changes in scores for anxiety, depression, family functioning, and quality of life (QoL) in pediatric patients with ICDs (20 patients).…”
mentioning
confidence: 99%